Do Princesses Wear Hiking Boots? - Gordon, Carl; Gordon, Mike (Flagstaff, AZ Rising Moon, 2003)
When a little girl asks her mother about princesses, she learns that they are much like herself.
Accelerated Reader
Keywords: Self-perception -- Fiction; Mothers and daughters -- Fiction; Princesses -- Fiction